2021
DOI: 10.1002/ecy.3428
|View full text |Cite
|
Sign up to set email alerts
|

Stronger predation intensity and impact on prey communities in the tropics

Abstract: The hypothesis that biotic interactions strengthen toward lower latitudes provides a framework for linking community-scale processes with the macroecological scales that define our biosphere. Despite the importance of this hypothesis for understanding community assembly and ecosystem functioning, the extent to which interaction strength varies across latitude and the effects of this variation on natural communities remain unresolved. Predation in particular is central to ecological and evolutionary dynamics ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 64 publications
2
42
0
1
Order By: Relevance
“…In the Madeira Archipelago, S. cretense is abundant from the surface to 50 m depth and constitutes an important fraction of coastal fish biomass [88]. Along with Thalassoma pavo (Linnaeus 1758), Boops boops (Linnaeus 1758) and Chromis limbata (Valenciennes 1833), S. cretense is one of the most common fish grazers [88] and thus plays an important ecological role by influencing the structure of fouling and shallow sessile communities in Madeira [89,90]. In this pilot study, the role played by S. cretense in the marina of Quinta do Lorde during RVFS trials matches this pattern and corroborates its importance in shaping fouling communities.…”
Section: Discussionmentioning
confidence: 99%
“…In the Madeira Archipelago, S. cretense is abundant from the surface to 50 m depth and constitutes an important fraction of coastal fish biomass [88]. Along with Thalassoma pavo (Linnaeus 1758), Boops boops (Linnaeus 1758) and Chromis limbata (Valenciennes 1833), S. cretense is one of the most common fish grazers [88] and thus plays an important ecological role by influencing the structure of fouling and shallow sessile communities in Madeira [89,90]. In this pilot study, the role played by S. cretense in the marina of Quinta do Lorde during RVFS trials matches this pattern and corroborates its importance in shaping fouling communities.…”
Section: Discussionmentioning
confidence: 99%
“…Biotic and abiotic factors not examined here are known to in uence epibenthic community structure and composition. While studies have demonstrated that predation may have strong impacts on epibenthic community composition (Vieira et al 2012;Oricchio et al 2016;Freestone et al 2021), its role in modulating exotic establishment is debated. In epibenthic communities, predation might serve to limit the establishment (Dumont et al 2011;Collin and Johnson 2014;Rogers et al 2016;Kremer and da Rocha 2016;Leclerc et al 2020) or dominance of exotic organisms, as predators tend to target poorly-defended, soft-bodied chordates (Kremer and da Rocha 2016), which were characteristics of the species that we found to be primary drivers of changes in exotic abundance and dominance.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated standard error and P-values for our model using the bootstrap method (boot.sims = 1000), and only considered percentile slope estimates to be significantly different from zero if P < 0.05 for five model iterations. It is not necessary to correct for multiple testing when using quantile regression because calculating slopes at multiple percentiles (τ values) is not repeated testing of the same statistical hypothesis (Spear and Mordecai 2018;Virta et al 2019;Freestone et al 2021).…”
Section: Component Covariation Among Speciesmentioning
confidence: 99%